Influence of breastfeeding on maternal blood pressure at one month postpartum - Kashiwakura, Ikuo; Ebina, Satoko (International Journal of Women's Health, 2012)
The benefits of breastfeeding for improved health and developmental outcomes in mothers and their infants have been widely recognized. The purpose of the present study was to assess whether feeding modes influence maternal blood pressure at one month postpartum. The pregnancy charts of 407 women who delivered at a birthing center in rural Japan between August 1998 and September 2007 were analyzed. The criteria for inclusion were low-risk, full-term pregnancy (duration, 37-42 weeks) resulting in spontaneous vaginal deliveries, intrapartum hemorrhage < 500 mL, and a healthy infant (Apgar score ≥ 8 at one minute). The subjects were classified into three groups based on feeding modes. The proportion of each mode was 28.3% in the breastfeeding group, 56.5% in the mixed-feeding group, and 15.2% in the formula-feeding group. The systolic blood pressure (SBP) in mothers at one month postpartum for each feeding mode was 118.4 ± 8.7 mmHg in the breastfeeding group, 120.6 ± 9.3 mmHg in the mixed-feeding group, and 122.0 ± 9.9 mmHg in the formula-feeding group. SBP at one month postpartum in the breastfeeding group was significantly lower than that in the other groups. No significant differences were observed in diastolic blood pressure in the three groups at one month postpartum. Breastfeeding resulted in lower SBP in mothers at one month postpartum compared with those using other feeding modes, thus indicating an effect of breastfeeding on maternal blood pressure.